2020
DOI: 10.3390/insects11010048
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Behavior of Asian Citrus Psyllid [Diaphorina citri (Hemiptera: Liviidae)] Nymphs and Adults on Common Weeds Occurring in Cultivated Citrus Described Using Electrical Penetration Graph Recordings

Abstract: Asian citrus psyllid, Diaphorina citri, transmits Candidatus Liberibacter asiaticus (CLas), the putative causal agent of Huanglongbing disease. Although they primarily feed on the phloem of Citrus and related plants, when grove or host conditions are unfavorable, D. citri may be able to use weed species as alternate food sources for survival. To explore this possibility, electrical penetration graph (EPG) recordings (18 h) were performed to investigate the feeding behavior of psyllid adults and nymphs on three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…L. asiaticus, but it has been recorded as an alternative host for the vector, Diaphorina citri, in Florida (where HLB is now endemic), with evidence that it may also support D. citri reproduction (Thomas and De León, 2011). Use of Ficus by D. citri has not been explored extensively outside of this one study, but several other recent reports document use of various alternative hosts by D. citri adults, likely as a source of water (Zhang et al, 2019;George et al, 2020). These ecological studies of D. citri host use suggest there are pathways for rare Ca.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…L. asiaticus, but it has been recorded as an alternative host for the vector, Diaphorina citri, in Florida (where HLB is now endemic), with evidence that it may also support D. citri reproduction (Thomas and De León, 2011). Use of Ficus by D. citri has not been explored extensively outside of this one study, but several other recent reports document use of various alternative hosts by D. citri adults, likely as a source of water (Zhang et al, 2019;George et al, 2020). These ecological studies of D. citri host use suggest there are pathways for rare Ca.…”
Section: Discussionmentioning
confidence: 86%
“…citri has not been explored extensively outside of this one study, but several other recent reports document use of various alternative hosts by D . citri adults, likely as a source of water ( Zhang et al, 2019 ; George et al, 2020 ). These ecological studies of D .…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that D. citri survival was extended in the presence of weeds compared with starvation conditions with and without water, indicating that adults could obtain water as well as food resources from all the weed species tested in this paper in the absence of a host. By using electrical penetration graph (EPG) recordings, George et al 29 found that D. citri adults may be able to use some weed species opportunistically as secondary host plants for acquiring water or alternate food. However, the adaptabilities of D. citri to the three weed species differed to a certain extend.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that under the conditions in which most EPG experiments are performed (laboratory, with properly maintained colonies not under Although we did not detect differences in phloemrelated parameters among color morphs, we did detect a pattern of blue-green ACP morphs ingesting more xylem sap than the other two morphs. The xylem is nutrient poor relative to the phloem, but does provide moisture and some micronutrients (George et al 2020). If the pattern we observed is biologically relevant, it could indicate that blue-green morphs may have different requirements for managing water balance and may try to compensate for this by modulating xylem sap intake.…”
Section: Discussionmentioning
confidence: 82%
“…´Valencia.` Since blue-green morphs perform better in activities that have higher energy demands, such as dispersal and immune response (Martini et al 2014;Hosseinzadeh et al 2021), we hypothesized that there would be more efficient and/or prolonged nutrient uptake bouts from phloem tissue by blue-green ACP relative to the other two color morphs. Psyllids feed from both xylem and phloem tissues, but use phloem sap as a primary source of nutrients (Hodkinson 1974;Antolinez et al 2017;Ebert et al 2018;George et al 2020) linking phloem directly to the psyllid energy demands. Phloem access and exploitation is also essential for CLas transmission.…”
Section: Introductionmentioning
confidence: 99%